Cervical pregnancy continuing to viable gestation. (18th April 2012) - Ryan, D Hayes; Khawaja, N; Higgins, S; Lenehan, P
Abstract : We report a case of a 32 year old para 0+0 transferred from a peripheral unit at 24+1 with PPROM. Ultrasound showed estimated fetal weight 615g, breech, anhydramnious and upper placenta. At 25+3 she developed severe lower back pain and antepartum haemorrhage >500mls. She underwent emergency caesarean for suspected placental abruption with consultant present. The uterus was markedly abnormal looking; the pregnancy lay below the anatomical uterus in a distended, thin walled segment. A female weighing 700g was delivered in good condition through a transverse lower uterine incision. A massive post partum haemorrhage of 6 litres followed and attempts at stabilisation of the patient were unsuccessful. Emergency hysterectomy was performed. Histology confirmed a cervical pregnancy. The patient had a further PPH 17 days later and underwent embolisation via interventional radiology but thereafter made a good recovery. Cervical pregnancy is a very rare form of ectopic pregnancy with an incidence of approximately 1 in 9000 deliveries. On a very rare occasion, a cervical pregnancy results in the birth of a live baby, typically the pregnancy is in the upper part of the cervical canal and manages to extend into the lower part of the uterine cavity. The most effective treatment of cervical pregnancy is still unclear, with medical rather than surgical therapy recommended with multidose methotrexate in patients who are hemodynamically stable.